(NnEMECKIE NARODNYE PESNI(B.s (NNOTYs - (Nn(B.(NaLEKSANDROWOJs (NPEREWOD^IKs ((NmOSKWAs (NlANXs (NpLANETA MUZYKAs, 2020)
(NsBORNIK SODERVIT TRIDCATX NEMECKIH NARODNYH PESEN (BXVIII-XIX (NWW(B.s
Keywords: (NrOMANSs